Young Adult Caregiver Strain and Benefits. (25th November 2019) - King McLaughlin, Jessica; Greenfield, Jennifer C; Hasche, Leslie; De Fries, Carson
Abstract: Young adult caregivers (YACs) of older adults are an often-overlooked subset of the caregiver population, though they make up more than a quarter of all caregivers. Because of their stage in life and their economic and work status, YACs (ages 21 to 40) are likely to face different caregiving challenges than other age cohorts of caregivers. Using the life course perspective and role conflict theory as foundational frameworks, this article compares the resources and strains of YACs with those of their middle-age caregiver (MAC) (ages 41 to 60) and older adult caregiver (OAC) (ages 61 and older) counterparts. Authors used data from a cross-sectional pilot study of caregivers recruited across one western state through community agencies. Through multivariate regression analysis, findings indicated that YACs reported more financial strain than MACs and OACs, despite being more likely to be employed. In contrast, YACs reported greater positive feelings toward caregiving than both MACs and OACs. These findings remained while controlling for employment status, education, and hours per week spent caregiving. Although YACs may find great value in caregiving, they may also be in more financially precarious situations. The article concludes with recommendations for caregiver support programs to reach YACs in the workplace.